Women, Democracy, and Globalization in North America
XII, 212 p. 4 illus.
Keywords: This book examines the impact of globalization upon Canada, Mexico and the United States. It investigates changes in the structures and practices of federalism, in public policies and practices of governance and politics, and in economic livelihoods in all three nations. It also provides comparisons of the effects of globalization on women's lives.